A three-year randomized clinical trial evaluating direct posterior composite restorations placed with three self-etch adhesives. Issue 1 (1st January 2021) - Sabbagh, Joseph; El Masri, Layal; Fahd, Jean Claude; Nahas, Paul
Abstract: Aim: To compare the clinical performance of composite restorations placed with a universal adhesive, one-step and two-step self-etch adhesives in class I and II posterior cavities. Materials and methods: In this in vivo study, 46 volunteers presenting with at least three carious lesions were included. Each participant received the three restorative systems: universal adhesive/nanofilled composite (Scotchbond Universal/Filtek Z350 XT: SBU/FZXT), one-step self-etch adhesive/microhybrid composite (G-aenial bond/G-aenial Posterior: GB/GP) and the two-step self-etch adhesive/nanohybrid composite (OptiBond XTR/Herculite Ultra: OBX/HU). The adhesives were all placed in self-etch mode. In total, 138 restorations were evaluated at baseline and at 6, 12 and 36 months using the modified United States Public Health Service criteria. Data were analysed using Kruskal–Wallis, Mann–Whitney U, Friedman and Wilcoxon non-parametric tests ( p < .05). Ninety-one restorations were evaluated at 36 months. Results: Seven restorations, three SBU/FZXT, three GB/GP and one OBX/HU failed during this study. The reasons for failure were marginal fracture and secondary caries. SBU/FZXT restorations showed significant marginal deterioration in all parameters. Overall success rates were: 93.5% (SBU/FZXT), 96.6% (GB/GP) and 96.8% (OBX/HU). Conclusions: After three years, the three restorative systems have comparable clinical effectiveness and success rates, except for the marginal integrity, that was suboptimal for both the SBU/FZXT and GB/GP restorations in comparison to the OBX/HU restorations.